‘Nobody believes you if you’re a bloke’: Barriers to disclosure and help-seeking for male forced-to-penetrate victims/survivors - Weare, Siobhan (International review of victimology, 2024)
Research on barriers that exist for male victims/survivors of sexual abuse in relation to disclosing their experiences is limited. This article shares qualitative data in relation to disclosure and help-seeking barriers encountered by male victims/survivors of female-perpetrated sexual abuse. Findings from semi-structured interviews conducted with 30 male victims/survivors in the United Kingdom about their forced-to-penetrate (FTP) experiences are discussed. FTP cases involve a man being FTP, with his penis and without his consent, the vagina, anus, or mouth of a woman. During their interviews, male victims/survivors shared multiple barriers which resulted in delayed, selective, limited, or no disclosure. These included; masculinity, feelings of shame and self-blame, struggling to understand and label experiences, concerns about the consequences of disclosure, and a lack of (knowledge about) support. These barriers are critically discussed and positioned within their broader contexts and consideration is given to how they can be overcome by those most likely to engage with male FTP victims/survivors.